ANALISIS POTENSI KEBANGKRUTAN PERUSAHAAN SUB SEKTOR PAKAIAN DAN BARANG MEWAH YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yulianus Palette; Mahmudin A.Sabilalo; Fahmi Sahlan (Sigma: Journal of Economic and Business, 2025)
This study aims to determine and analyze the Altman, Grover and Springate models in detecting potential bankruptcy of clothing and luxury goods sub-sector companies for the 2021-2023 period and a comparison of the level of accuracy in detecting potential bankruptcy. The research method used descriptive quantitative research method, using 5 companies as research samples selected based on purposive sampling technique. The results showed that the Altman model detected 2 bankrupt companies, 1 gray area and 1 not bankrupt, the Grover model detected 2 bankrupt companies, and 3 bankrupt companies, while the Springate model detected all companies in potential bankruptcy. The highest accuracy rate by Grover model is 40% with 60% error, Altman accuracy rate is 20% with 60% error and Springate 0% with 100% error rate.